Pelaksanaan Pengawasan Otoritas Jasa Keuangan (Ojk) Dalam Mengawasi Bank Milik Pemerintah Kota Makassar - Saad, Sardiman; Usman, Jaelan; Burhanuddin, Burhanuddin (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to find out the preventive and repressive supervision of the Financial Services Authority (Otoritas Jasa Keuangan – “OJK”) to Government-owned Banks in Makassar City. The method used in this study was descriptive qualitative with five informants. The data collection techniques included observation, interviews and documentation. The results of the study showed that the implementation of preventive supervision of financial services authorities (Otoritas Jasa Keuangan – “OJK”) in supervising Makassar City government banks regarding socialization, work plans, and resources that had run optimally. Also, Repressive supervision of the audit post and inspection had  run maximally. Thus, the result of this study showed that the supervision carried out by the financial services authority run maximally. Keywords:  Supervision, financial services authority, government-owned bank